MOBILE LEARNING: NEW ERA IN MALAYSIA - Hamzah, Mahizer bin (Pendidikan Dasar, 2009)
Abstract: Mobile learning (m-learning) is not a new phenomenon. It gives opportunity to learn without access limitation. Compared with face-to-face, mobile learning can be done without the need for a particular physical infrastructure to access information especially for those who live in remote area. By having a mobile gadget such as the mobile phone, PDA (personal digital assistants) or portable computer, information can be accessed at anytime and where. Hence, this paper will discuss on the potential of m-learning as a tool for learning.